Study on the correlation between resilience, social support and quality of life in patients with inflammatory bowel disease - Yu, Yanfei; Zheng, Yeping; Wu, Lingsha (Frontiers in Psychiatry, 2026)
BackgroundInflammatory bowel disease (IBD) seriously affects the physical and mental health of patients. Resilience can enhance patients’ coping abilities and improve their health to a certain extent, as well as their quality of life. Social support is closely related to quality of life. However, there is currently a lack of research on the relationship between resilience, social support and quality of life in patients with IBD.ObjectiveTo explore the mediating role of social support between resilience and quality of life in patients with IBD.MethodsThis study was a cross-sectional study. A total of 207 IBD patients from the Department of Gastrointestinal Surgery of a tertiary first-class hospital in Jiaxing City were selected by convenience sampling from August 2023 to April 2024. They were investigated using a general information questionnaire, Connor-davidson Scale (CD-RICS), Quality of Life Scale, and Social Support Rating Scale. The relationships among resilience, social support, and quality of life were analyzed. A total of 207 questionnaires were distributed, and 207 valid questionnaires were recovered.ResultsThe average age of 207 patients with inflammatory bowel disease was (44.24 ± 14.10) years old. The total resilience score of IBD patients was (61.58 ± 22.37) points, the total social support score was (43.37 ± 11.46) points, and the total quality of life score was (182.22 ± 31.94) points. The mediating effect analysis showed that social support played a partial mediating role between resilience and quality of life in IBD patients, accounting for 32.35% of the total effect.ConclusionThe quality of life of IBD patients is at a moderate to high level. Resilience in IBD patients can directly affect their quality of life, and also indirectly affect it through social support. Medical staff and society should take measures to improve the social support of IBD patients, thereby helping them live better lives.